PENGARUH LAMA SIMPAN PADA SUHU RUANG TERHADAP KADAR PROTEIN DODOL TAPE KULIT UMBI UBI KAYU - Wikanastri . Hersoelistyorini; Didik Sumanto; Lugman . Najih (Jurnal Pangan dan Gizi, 2010)
The carbohydrate’s content of cassava is quite high, so it is possible to be used as the source of energy for microorganism in fermentation process. The result of fermentation in cassava can be processed as food product in the form of ‘dodol’. The aim of this research to find out whether there is any difference of protein content based on the duration of saving the fermented cassava in the normal temperature. The result of research based on the data which were tested using Kruskal Wallis test showed that p-value = 0,009; if α = 5% is applied, so that p-value < α. There is a difference in the protein content of the dodol of tapai cassava product, which is saved in the normal temperature. Key words : dodol, cassava, fermentation.